2024
DOI: 10.3389/frai.2024.1349668
|View full text |Cite
|
Sign up to set email alerts
|

Digital accessibility in the era of artificial intelligence—Bibliometric analysis and systematic review

Khansa Chemnad,
Achraf Othman

Abstract: IntroductionDigital accessibility involves designing digital systems and services to enable access for individuals, including those with disabilities, including visual, auditory, motor, or cognitive impairments. Artificial intelligence (AI) has the potential to enhance accessibility for people with disabilities and improve their overall quality of life.MethodsThis systematic review, covering academic articles from 2018 to 2023, focuses on AI applications for digital accessibility. Initially, 3,706 articles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Studying the impact of AI tools on the educational process, it was found that it leads to more personalized learning landscape (Lin et al, 2023), automation of administrative tasks, such as grading and scheduling (Rahm, 2023), and providing more access to education through online learning platforms, digital resources, or intelligent tutoring systems (Chemnad & Othman, 2024). According to the survey results, AI enhances students' learning outcomes, automates the routing tasks, and makes the educational process more accessible to students with disabilities.…”
Section: Encouragement Of Innovationmentioning
confidence: 99%
“…Studying the impact of AI tools on the educational process, it was found that it leads to more personalized learning landscape (Lin et al, 2023), automation of administrative tasks, such as grading and scheduling (Rahm, 2023), and providing more access to education through online learning platforms, digital resources, or intelligent tutoring systems (Chemnad & Othman, 2024). According to the survey results, AI enhances students' learning outcomes, automates the routing tasks, and makes the educational process more accessible to students with disabilities.…”
Section: Encouragement Of Innovationmentioning
confidence: 99%
“…This omission underscores the need for real-world applications and solutions to better understand and tackle these barriers. Evidence in the literature indicates a prevalent focus on AI-driven digital accessibility for visual disabilities, which highlights a significant gap in addressing other types of disabilities [37]. Individuals with disabilities often experience limited access to information and communication technology (ICT) and internet connectivity, which can be attributed to various factors such as financial constraints, physical impediments, low levels of digital literacy, and inadequate support [38].…”
Section: Introductionmentioning
confidence: 99%